Estimation of Weed Biomass as Forage Production under Oil Palm Plantation - Nur Rochmah Kumalasari; Andriyani Prasetiyowati; Sunardi Sunardi; Suryahadi - (School of Postgraduate Studies, Diponegoro Univer, 2023)
Palm oil plantations have the potency to provide forage as a source of energy for livestock. The objective of this research was to estimate the production and quality of weeds under palm plantation as ruminant feed. Identification was conducted to find out information about botanical composition, production and nutritional content to estimate potential forage. The study was conducted using a randomized block design with 2 blocks of 6- and 8-years old palm and 10 sample plots. The research parameters were botanical composition, weed dominance and diversity, and also forage production potency. The results showed that 19 species from 11 families were found and dominated by gramineae. The weed botanical composition and diversity level was affected by oil palm plantation age. On the 8 years old oil palm plantation, the number of weed species and diversity level were decreased, reaching 10 species and H’ 2.41 while on the 6 years old were 13 species and H’ 3.14. Based on the type of weed, Paspalum conjugatum P.J. Bergius is a weed that has the potential to be used as the highest forage as ruminant animal feed with an estimated production of 730.42 kg ha-1 of fresh biomash. The estimation of weed production ruminant forage was dominated by grass that had up to 1.87 ton ha-1 of fresh biomash.